Digitalization of Public Accountability: Integrating Digital Literacy into Public Sector Audit and Accounting Practice - Dini Indri Irianti; I Gusti Ayu Purnamawati; Gusti Ayu Rencana Sari Dewi (Research Horizon, 2026)
Amid rapid digital governance transformation, demands for transparency and accountability are increasing. This study aims to analyze the role of digital literacy in strengthening public sector audit and accounting practice in the era of digitalization, with a view to enhancing government accountability in Indonesia. Employing a narrative literature review approach, the study synthesizes theoretical and empirical perspectives drawn from recent literature. The findings indicate a paradigmatic shift in public accountability from a hierarchical model to a multi-stakeholder network enabled by digital technology. Digital literacy is a key determinant of effective implementation in enhancing transparency and accountability; however, a gap remains between required competencies and existing human resource capacity and educational curricula. In Indonesia, digitalization faces challenges including infrastructure disparities, uneven digital literacy among civil servants, and system fragmentation due to decentralization. This study recommends a multidimensional approach to integrating digital literacy into public sector audit and accounting, including the development of a national competency framework, curriculum reform, and context-sensitive implementation strategies. The findings contribute theoretically and practically to the advancement of public accountability by proposing a conceptual framework that positions digital literacy as a moderating variable in the relationship between digital technology and accountability enhancement.